De la ventriloquie au trauma - Marc Amfreville (Sillages Critiques)
This article aims at showing that imitation, far from being only a theme that pervades American literature from the start (Charles Brockden Brown, Ambrose Bierce) to its most recent developments (DeLillo), constitutes a defining structure. Drawing extensively from Freud, but also to a lesser extent from Derrida, this paper, jointly interrogating the figure of the biloquist villain in Wieland, the picture of the aftermath of the Civil War in “Chickamauga” and the 9-11 icon of destruction in Falling Man, endeavors to highlight the parallel and converging lines of psychoanalysis and literature as regards the representation of trauma.